Bringing the Legend to Life:: Tourist Experience and Cultural Interpretation of the Sangkuriang Legend at Mount Tangkuban Parahu - Aditya Rizki Rinaldi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2025)
Mount Tangkuban Parahu is a tourist destination that offers natural beauty and has strong cultural value through the legend of Sangkuriang. These legendary narratives shape tourists' expectations before they visit and influence how they interpret the physical landscape they observe. This research aims to analyze the experiences of tourists who already have an understanding of the Sangkuriang story and identify the gap between expectations and the reality of cultural interpretation in the field. The method used is a qualitative approach through in-depth interviews and participant observation with tourists who have a background in understanding this legend. The research results show that tourists have high expectations for culture-based tourism experiences, but they find limitations in presenting legendary narratives at locations. The lack of information boards, the lack of storytelling-based tour guides, and the absence of cultural attractions that support immersive experiences are the main obstacles in creating a more immersive tourism experience. In addition, tourists feel that visual interpretation and landscape elements have not been fully optimized to strengthen the connection between the Sangkuriang story and tourist destinations. Therefore, innovative strategies are needed to improve cultural interpretation on Mount Tangkuban Parahu, such as strengthening the role of tour guides, developing thematic tourist routes, and utilizing digital technology such as augmented reality (AR) and interactive tourism applications. In addition, collaboration with local communities and academics is an important step in enriching a more authentic and sustainable cultural narrative. By implementing this strategy, Mount Tangkuban Parahu has great potential to become a leading cultural tourism destination that is visually attractive and provides an educational and interactive experience for tourists.